Industrialización de la pulpa del Guarango (prosopis pallida) para la producción de Café. - Manzaba Granda, Jonathan Andrés (2019)
The present research was carried out of Latacunga canton, Eloy Alfaro parish, Salache Bajo neighborhood, of Technical University of Cotopaxi, in Agroindustrial Engineering career laboratories, whose main objective was to industrialize the pulp of guarango ( Prosopis pallida ) to make coffee. Applied methodology to development the research was experimental and quantitative, where different processes were carried out prior grinding, they were roasted at 3 different temperatures (160ºC, 165ºC and 170º) and at different times (60 , 55 and 50 minutes), finally, the roasted grain was ground . An experimental model of completely random block design was applied, in addition a survey to 30 students of Agroindustrial Engineering career with two repetitions. This was allowed, through a statistical analysis in the Infostat software, the determination of the best treatment resulting in the treatment t1 (a1b1) which corresponds to Seeds + 160ºC x 60 minutes, in evaluated variables: smell, color, taste, texture and acceptability. In addition, a final quality product was obtained within the established parameters by INEN 1123 Standard, guaranteeing freshness and safety of the product, for which laboratory analysis of the best treatment was carried out and the microbiological analysis was reported. is within the established parameters in INEN 1123 regulation, wherethe Escherichia coli count using a PEEMi / LA / 20 INEN 1529-7 method, the result obtained was <10 cfu / g; as well as on detection of Coliformes applying a PEEMi / LA / 20 INEN 1529-7 method, a value <10 was obtained. Finally, in the count of Mesophiles with the method PEEMi / LA / 01 INEN 4833, the value was <10. The chemical analysis reported a humidity of 0.28%, being allowed according to the INEN 1123 standard up to a maximum of 5, while for the percentage of ash, the value analyzed was 4.02, with a maximum of 5. The cost of production in a presentation of 0.225Kg was $ 12.92